Findings in physical examination of the external genitalia in pediatric age − different is not always pathological - Part II (female) - Pinto, Nuno Teles; Costa, Diana Morais; Marinho, Ana Sofia; Pinto, João Moreira (BIRTH AND GROWTH MEDICAL JOURNAL, 2021)
Introduction: Findings in the physical examination of the external genitalia in children are often a source of concern and anxiety for parents and caregivers. Due to the proximity and role in child’s periodic surveillance, the family physician is in a privileged position to identify and initially provide guidance on these situations, key for the success of future interventions. Objectives: To review available evidence on the main variations and anomalies of the external female genitalia in pediatric age, focusing on diagnosis and clinical approach in primary health care. Results: In most cases, anomalies of the prepubertal female external genitalia are only variants of normal and/or do not significantly affect function, hence not requiring intervention other than clinical surveillance – e.g., fusion of labia minora. However, others require referral to secondary health care − like congenital vaginal obstruction or clitoral hypertrophy –, with early intervention being crucial for the success of implemented measures in some cases. Conclusion: Genital pathology in prepubertal children is most often diagnosed by systematic and careful physical examination and usually has a favorable outcome. It is important to distinguish variants of normal from situations requiring more specialized assessment, in order to optimize health care system resources without overloading it and decrease parental anxiety.